Polycyclic aromatic compounds-modified graphitic carbon nitride for efficient visible-light-driven hydrogen evolution - Li, Kui; Sun, Miao; Zhang, Wei-De (Carbon (New York), 2018)
Polycyclic aromatic compounds with strong conjugated effect, possess the advantage of improving electronic polarizability, thus accelerating the electron transportation. Here, a facile copolymerization between urea and polycyclic aromatic compounds (benzoic acid, naphthoic acid and anthroic acid) has been applied to constructing aromatic rings-grafted graphitic carbon nitride (GCN) photocatalysts. Incorporation of aromatic rings in the GCN network is an effective protocol to extend its π-conjugated system for visible light harvesting and improves the charge transfer efficiency for prolonging lifetime of photogenerated charge carriers in photocatalytic reactions. The corresponding characterization methods demonstrate that the aromatic rings-modified GCN can effectively narrow the bandgap to favor broad band visible light absorption and suppress recombination of electrons and holes. Remarkably, the moderate conjugated effect of aromatic rings (naphthalene) is crucial to promote charge separation. The developed naphthalene-grafted GCN achieves the highest water splitting performance with hydrogen evolution rate up to 102.1 μmol h−1, nearly 3.5 times of that of the GCN, and apparent quantum efficiency reaches 5.6% at 450 nm. This finding reveals that the conjugated effect of aromatic rings is significant to control photocatalytic property and brings new ideas for designing aromatic system-modified GCN as highly active photocatalysts towards solar-to-chemical energy conversion. This study reports the preparation, characterization and photocatalytic activity of aromatic rings-grafted graphitic carbon nitride (GCN) photocatalysts, which display enhanced visible light absorption and improved separation of charge carriers due to the extended π-conjugated system, and thus the high hydrogen evolution rate. [Display omitted]